Analisis Kadar Nrf2 plasma Pada Tikus dengan Defisisensi Vitamin B12 - Endin Nokik Stujanna; Irena Ujianti; Etty Farida Mustifah (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2021)
Background. Vitamin B12 deficiency is a significant problem, particularly in developing countries. The increasing complexity of the Vitamin B12 molecule, the deficiency condition, causes a complex cell level disorder. The clinical manifestation of vitamin B12 deficiency is anemia, but it is believed that due to the complexity of vitamin B12, there are still other molecular disorders. This study aims to establish the pathway of damage caused by vitamin B12 deficiency in the Nrf2 molecule. Methods. An animal experiment involving 12 male Sprague Dawley rats were randomly divided into control and 16-week treatment. There are two research groups, namely the control group and the treatment group. The control group was given a standard diet, while the treatment group was assigned a vitamin B12 deficiency diet. At the end of treatment, The levels of vitamin B12 in the liver tissue and plasma NRF2 were measured. Statistical Analysis. Nrf2 and vitamin B12 levels were statistically analyzed using the Student's T-test, and the correlation between vitamin B12 and Hb was analyzed using the Spearmen test. Data that cannot use by Independent T-test were tested using the Mann Whitney test. Results/Conclusion. There was no significant difference between the control and treatment groups on plasma Nrf2 levels (4.02 ± 0.59 pg/ml vs 3.34 ± 0.55 pg/ml; p = 0.07) and tissue vitamin B12 (0.0035 ± 0.0016 µg/ml vs 0.0030 ± 0.0006 µg/ml ; p = 0.8). Keywords: Nrf2 Plasma, Defisiensi, Vitamin B12